The Influence of Emotional Intelligence on Toxic Behavior in Playing the Online Game Mobile Legends - Sabilla Rosyad, Ridhia; Hidayanto, Syahrul (Green Publisher, 2024)
This study aims to determine whether there is an influence of the emotional intelligence of vocational students on toxic behavior in playing mobile legends online games. This study used a survey method and data collection was carried out using questionnaires. The population in this study is students of SMK Karya Guna 2 Bekasi who play Mobile Legends online games for at least 1 year. The research sample was selected based on a purposive sampling technique with 94 respondents and using SPSS Version 25. The percentage of emotional intelligence results of SMK Karya Guna 2 Bekasi students is 80% to 68% and is in a strong category, (2) the results of the percentage of toxic behavior are 56% to 28% and are in the sufficient to the weak category, (3) Based on a simple linear regression test, there was a significant negative influence between emotional intelligence on toxic behavior with a regression coefficient value of -0.260 and was in the weak category with a value of -0.370. The research results are only an initial description of the phenomenon. More in-depth research and more comprehensive data collection techniques are needed. The higher the emotional intelligence that students have, the lower the toxic behavior carried out by students, conversely the higher the toxic behavior carried out by students, the lower the emotional intelligence that students have. Currently, emotional intelligence is very much needed in students. The current phenomenon is that many students engage in toxic behavior in the online game that is widely downloaded, namely Mobile Legends. Based on the literature review, there is a gap in the research theme of emotional intelligence towards toxic behavior.